Analýza vývoje vegetace krkonošské tundry s využitím časové řady ortofot - Pajmová, Petra (Univerzita Karlova, Přírodovědecká fakulta, 2022)
Analysis of tundra vegetation developement using a time series of ortoimages in the Krkonoše Mountains Abstract The aim of this study is to analyse changes in arctic-alpine tundra vegetation in the Krkonoše Mountains using archival and current aerial imagery with red, green and blue bands and spatial resolution of 0.5 m. Three small areas of interest (cca 100  100 m) with different types of vegetation and a one larger area of the eastern tundra were studied. Several classification methods (Maximum likelihood classification, Random forest and object-based classification) were tested to obtain the best classification results. For more detailed analysis of grass species development, unsupervised classification and extended time series (5 orthoimages) were used for the area of Bílá louka. Classification were executed in softwares ENVI 5.5 and R 4.2.1. The highest overall accuracy of the 2020 image classifications were over 70% in all study areas, in some cases over 80%. With the exception of the Luční hora area (58%), the best overall accuracies for 2004 image were above 65%. After comparing classification results between years 2004 and 2020, a possible development trend was revealed. But due to low accuracy of the 2004 data classifications, this cannot be reliably demonstrated. Key words: classification,. Analýza vývoje vegetace krkonošské tundry s využitím časové řady Cílem této studie je analyzovat změny vegetac alpínské tundry v Krkonoších s využitím archivních a současných leteckých snímků s červeným, zeleným a modrým pásmem a prostorovým rozlišením 0,5 m. tři  rozdílnými typy vegetace a dále širší území východní tundry epších výsledků klasifikace bylo testováno několik klasifikačních objektově orientovaná klasifikace) podrobnější analýzu travních druhů byla pro oblast použita neřízená a rozšířená časová řada ortofot (5 časových horizontů) Nejvyšší celková přesnost byla ve všech studovaných oblastech přes 70 %, v některých případech přes 80 %. výjimkou Luční hory (58 %), byly p nejlepší celkové přesnosti ...